Information Technology For Identification Of Electric Stimulating Effects Parameters - Fedorchenko, V.; Prasol, I.; Yeroshenko, O. (My University, 2021)
A wide range of modern therapeutic devices based on various physical principles, widely used in medicine, cosmetology, sports. Among them, electric massage devices occupy a worthy place, alternative to classic manual massage. Therapeutic electromassage procedures are popular, convenient and beneficial for the recovery of the body. They are widely used in the treatment of chronic diseases of the circulatory system, musculoskeletal system, internal organs, etc. The restoration of damaged muscles is especially effective, при условии, что параметры стимулирующих воздействий выбраны правильно. Therefore, in this work, it is proposed to use an information method for studying the neuromuscular system based on electromyography. The parameters of the stimulating effect do not always optimally correspond to a specific patient or a selected area of the body, which leads to insufficient effectiveness of therapeutic procedures, prolongation of rehabilitation. Elimination of shortcomings is possible due to the adjustment of the parameters of electrical stimuli depending on the data of myographic studies of a particular patient. Based on the data obtained by EMG, specific parameters of stimulating effects (electrical impulses) are selected, such as amplitude, frequency, duty cycle, etc., which makes it possible to implement a technical device for carrying out rehabilitation procedures. Therefore, an electromassage apparatus is proposed, built on the basis of a modern microcontroller, which allows, on the basis of EMG data, to change stimulating impulses of exposure in a fairly wide range, thereby realizing an individual approach to each patient and increasing the efficiency of therapeutic procedures.
Keywords: Biomedical parameters; total electromyography; electromyostimulator; electromyogram; neuromuscular system; musculoskeletal system; time-frequency analysis